Research on Social Resilience Construction and Climate Adaptation Strategies for Extreme Rainfall Risks - Huang, Chungchen (International Journal of Social Sciences and Public Administration, 2026)
In recent years, global climate change has led to an increase in the frequency and intensity of heavy rainfall, posing a significant threat to the survival and development of cities. Traditional disaster management methods are difficult to effectively solve the increasingly complex urban flood problems. From the perspective of rainstorm disaster, this paper analyzes the relevant measures and methods to enhance urban adaptability and improve climate resilience. On the basis of identifying new changes in extreme precipitation disasters and their impacts on existing systems at all levels, this article forms a main idea for cultivating social resilience from the perspectives of absorption capacity, adaptability, and resilience. Based on this, it explores countermeasures and suggestions for the coordinated response of engineering and non engineering measures to climate change, and finally proposes institutional arrangements and policy designs for the coordination of the two. In conclusion, enhancing regional resilience and actively adapting to climate change at a higher scale is one of the effective ways to reduce the risk of rainstorm disasters, and attention should be paid to the combination of concept updating, mechanism design and multi-party participation.